Kajian Sistem Deteksi Dini pada saat Pandemi COVID-19 - Nurmajid Setyasaputra (Jurnal Sistem Cerdas, 2021)
One of the increasing cases of COVID-19 is due to the large crowd. The crowd that occurred during the last quarter of 2020 occurred as a result of the easing of the PSBB to revive the community's economy, rife demonstrations, and other activities or events with large numbers of people. This is very worrying, coupled with the limited facilities and health workers to treat COVID-19 patients for those with severe symptoms. Therefore, an early detection system is needed by utilizing existing technology, especially for cities that have implemented smart cities and become red zones. So that this system can be an early warning or early detection for stakeholders to make decisions more quickly to prevent additional cases.